Strategi Pembelajaran Shalat oleh Guru Penddidikan Agama Islam Terhadap Anak Tunadaksa di SDLB Negeri Pangkalpinang - Ruzaipah; Muhammad Munir; Agus Ma’sum Aljauhari (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2020)
The focus of the study is on the Islamic religious education strategy for disabled children. Disabled children are those with orthopedic disorders or disorders of normal function in bones, muscles, and joints because of congenital birth, illness, or accident. So that any movement or walking is necessary. Physical disability of disabled children causes them to go through obstacles to performing the prayers. With disabilities different from other children, the education teachers of Islam guide disabled children in performing prayers. The study aims to describe the learning strategy and to provide more information about the weaknesses and strengths of the learning strategy used by the Islamic religious education teacher. The study uses descriptive types of qualitative research. Data is obtained through methods of interviews, observation, and documentation. Research shows that the strategy used by the Islamic education teacher in The State SDLB of Pangkalpinang is a factually, contextual, and cooperative learning strategy. The weaknesses of these three strategies are that they cannot be used to students with hearing problems, teachers must be more intense in their guidance, and implementation requires considerable time. The advantage is that teachers can control the sequence and the broadness of the material, the study is more fun and less boring, and communicate with others.